Application of Qualitative Characteristics to Evaluate Misstatements in Financial Statements: Evidence from Factual Audit Data - Masiulevičius, Audrius; Lakis, Vaclovas (Ekonomika, 2022)
The auditor should use qualitative characteristics, which describe the essence of misstatement, while assessing identified misstatements. Final decision depends on the professional judgment made by the auditor, however, auditors may make erroneous decisions or be biased. Previous theoretical research highlighted problems with the application of qualitative characteristics. However, factual audit data is confidential and usually not available for researchers to examine, therefore previous research mostly relied on surveys or experiments and there is little evidence on how auditors behave during real audits (rather than simulations). One audit company agreed to provide us with factual data for this research. The aim of the research is to examine the application of primary qualitative characteristics based on factual audit data. During the research, the audits performed in one Lithuanian audit company for the financial years 2019–2020 were examined as well as summarized official (publicly available) data about audit companies in Lithuania and audits performed by them for 2018–2020 financial years were examined. Firstly, most important primary qualitative characteristics, as well as secondary commonly used characteristics, were singled out. Our further investigation, based on received 2019–2020 factual audit data revealed that some auditors still do not apply primary qualitative characteristics in all cases. Even though we investigated one company and we cannot directly extrapolate results for the whole audit market, but our results are in line with the official and publicly available information about audit companies in Lithuania. Thus, we conclude that our results partly reflect truthful view of factual behavior of audit companies in Lithuania. These results also confirm theoretical research that qualitative characteristics are not sufficiently appreciated.